The Drosophila larval salivary gland, a simple and elegant model system to understand secretory organ development and function. - Kim, J.H.; Shoemaker, A.M.; Hutchings, K.A.; Shinde, S.; Andrew, D.J. (Current opinion in insect science, 2026)
Understanding how cells are specified and subsequently undergo the morphological and physiological specializations required to build functional organs has long been a goal of developmental biology studies. The Drosophila salivary gland (SG), a simple epithelial tubular organ specialized for secretion, has proven an excellent model for understanding how the complex process of organogenesis is orchestrated. The transcription factors (TFs) and signaling pathways that determine where in the developing embryo SGs form and how many cells contribute to each of the specialized cell types have been discovered. The early-expressed downstream SG TFs have been shown to regulate their own and each other's expression and to also activate downstream target genes directly linked to the mechanical forces of tube morphogenesis and/or to secretory function. Indeed, recent discoveries reveal that the larval SG, long considered an excellent model for exocrine secretion, also functions as an endocrine organ to support overall animal growth, and undergoes massive apocrine secretion as its final act to protect the developing pupa from microbial infection.